1993
DOI: 10.1128/aac.37.11.2412
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo antifungal activities of D0870, a new triazole agent

Abstract: In vitro and in vivo antifungal activities of D0870 were evaluated in comparison with those of fluconazole. D0870, which is the R-enantiomer of IC1195,739, was found to be the mycologically active enantiomer by comparing the activities of D0870 with those of M16355 (S-enantiomer of IC1195,739). D0870 showed a broad spectrum of antifungal activity and MICs and minimum antibiotic concentrations 4-to 2,000-fold lower in synthetic amino acid medium (fungal) agar than those of fluconazole for various fungi. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 17 publications
1
24
0
Order By: Relevance
“…(1, 7, 10, 11, 13), Cryptococcus neoformans (10,13), Histoplasma capsulatum (11), Blastomyces dermatitidis (12), and Coccidioides immitis (2). It has shown activity against human oropharyngeal candidosis even in a few patients with fluconazole-resistant disease (1,7).…”
Section: Discussionmentioning
confidence: 99%
“…(1, 7, 10, 11, 13), Cryptococcus neoformans (10,13), Histoplasma capsulatum (11), Blastomyces dermatitidis (12), and Coccidioides immitis (2). It has shown activity against human oropharyngeal candidosis even in a few patients with fluconazole-resistant disease (1,7).…”
Section: Discussionmentioning
confidence: 99%
“…1H-1, 2, 4-triazol-1-yl]-3-(1H-1, 2, 4-triazol-1-yl) propan-2-ol, is a new antifungal agent that is active orally and parenterally against a wide range of systemic mycosis, even in the immunocompromised models [31]. We previously reported that D0870 induced plasma concentrationdependent QT prolongation and sudden death due to ventricular fibrillation (VF) associated with torsades de pointes (TdP) in a dog study using loading (50 mg/kg) and maintenance (5 mg/kg/day) doses with long-term ambulatory electrocardiographic monitoring [19].…”
Section: D0870 Which Is Chemically (R)-(+)-2-(2 4-difluorophenyl)-1mentioning
confidence: 99%
“…Several models of experimental murine infections were used for the in vivo testing of D0870. Vaginal (11,17) and disseminated (11,12,23) candidiasis caused by C. albicans, disseminated (12,23) and pulmonary (17) cryptococcosis, cryptococcal meningitis (9), pulmonary blastomycosis (7), hematogenous aspergillosis (23), and coccidiodomycosis (8) in normal and immunosuppressed mice responded more favorably to D0870 than to fluconazole. The activity of D0870 in experimental candidiasis caused by Candida species other than C. albicans was variable.…”
mentioning
confidence: 99%
“…Nevertheless, our study is in agreement with recent favorable reports on the activity of D0870 against various fungi. D0870 has a broad spectrum of in vitro antifungal activity against Candida species (12,19,23), Cryptococcus neoformans (12,19,23), Blastomyces dermatitidis (7,20), Aspergillus fumigatus (18,20,23), and other molds (20). The MICs of D0870 against Candida krusei (19) and Torulopsis glabrata (4,20) were higher than those against various Candida species.…”
mentioning
confidence: 99%